Single low-dose primaquine for blocking transmission of Plasmodium falciparum malaria - a proposed model-derived age-based regimen for sub-Saharan Africa. - Taylor, W; Naw, H; Maitland, K; Williams, T; Kapulu, M; D'Alessandro, U; Berkley, J; Bejon, P; Okebe, J; Achan, J; Amambua, A; Affara, M; et al. (BioMed Central, 2018)
Background In 2012, the World Health Organization recommended blocking the transmission of Plasmodium falciparum with single low-dose primaquine (SLDPQ, target dose 0.25 mg base/kg body weight), without testing for glucose-6-phosphate dehydrogenase deficiency (G6PDd), when treating patients with uncomplicated falciparum malaria. We sought to develop an age-based SLDPQ regimen that would be suitable for sub-Saharan Africa. Methods Using data on the anti-infectivity efficacy and tolerability of primaquine (PQ), the epidemiology of anaemia, and the risks of PQ-induced acute haemolytic anaemia (AHA) and clinically significant anaemia (CSA), we prospectively defined therapeutic-dose ranges of 0.15–0.4 mg PQ base/kg for children aged 1–5 years and 0.15–0.5 mg PQ base/kg for individuals aged ≥6 years (therapeutic indices 2.7 and 3.3, respectively). We chose 1.25 mg PQ base for infants aged 6–11 months because they have the highest rate of baseline anaemia and the highest risks of AHA and CSA. We modelled an anthropometric database of 661,979 African individuals aged ≥6 months (549,127 healthy individuals, 28,466 malaria patients and 84,386 individuals with other infections/illnesses) by the Box–Cox transformation power exponential and tested PQ doses of 1–15 mg base, selecting dosing groups based on calculated mg/kg PQ doses. Results From the Box–Cox transformation power exponential model, five age categories were selected: (i) 6–11 months (n = 39,886, 6.03%), (ii) 1–5 years (n = 261,036, 45.46%), (iii) 6–9 years (n = 20,770, 3.14%), (iv) 10–14 years (n = 12,155, 1.84%) and (v) ≥15 years (n = 328,132, 49.57%) to receive 1.25, 2.5, 5, 7.5 and 15 mg PQ base for corresponding median (1st and 99th centiles) mg/kg PQ base of: (i) 0.16 (0.12–0.25), (ii) 0.21 (0.13–0.37), (iii) 0.25 (0.16–0.38), (iv) 0.26 (0.15–0.38) and (v) 0.27 (0.17–0.40). The proportions of individuals predicted to receive optimal therapeutic PQ doses were: 73.2 (29,180/39,886), 93.7 (244,537/261,036), 99.6 (20,690/20,770), 99.4 (12,086/12,155) and 99.8% (327,620/328,132), respectively. Conclusions We plan to test the safety of this age-based dosing regimen in a large randomised placebo-controlled trial (ISRCTN11594437) of uncomplicated falciparum malaria in G6PDd African children aged 0.5 − 11 years. If the regimen is safe and demonstrates adequate pharmacokinetics, it should be used to support malaria elimination.